Adaptive Strategies of Firms in High Velocity Environments: The Case of B2b Electronic Marketplaces - Ganesh, J. (Institutional Knowledge at Singapore Management University, 2004)
The adaptation-evolution strategies of firms have been a major area of interest. Internet based businesses operate in highly unstable environments witnessing shakeouts and changes in the industry structure. In this paper, we focus on the adaptive strategies and paths of adaptation of independent B2B marketplaces. The independent B2B marketplaces have undergone tremendous change with regard to their business models and products/services. Since their inception as pure market makers, these marketplaces have morphed into integration service providers with market making being one of the functions. What makes the adaptive strategies of B2B marketplaces interesting is the extremely short time period within which these changes happened. The research uses the case study methodology to identify the adaptive strategies of B2B marketplaces in terms of their product/service class evolution. The results based on the case studies suggest a three-stage adaptation model wherein the marketplaces progress through stages such as aggregation, transactions and integration. [PUBLICATION ABSTRACT]